2023
DOI: 10.1097/wno.0000000000001899
|View full text |Cite
|
Sign up to set email alerts
|

Complications of the Superior Eyelid Endoscopic Transorbital Approach to the Skull Base: Preliminary Experience With Specific Focus on Orbital Outcome

Abstract: Background: The endoscopic superior eyelid approach is a relatively novel mini-invasive technique that is currently investigating for skull base cancers. However, questions remain regarding specific approach-related complications when treating different skull base tumors. This study aims to analyze any surgical complications that occurred in our preliminary consecutive experience, with specific focus on orbital outcome. Methods: A retrospective and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Since TOAs are minimally invasive approaches, in-depth anatomical knowledge is required to recognize the main landmarks despite the unusual surgical perspective, especially for young trainees. This corridor is indicated in the cases of proptosis and lesions located lateral to the CN II [ 8 , 13 , 17 , 19 , 20 , 23 , 24 , 31 , 39 , 53 , 54 , 57 ]. The TOAs offer a good exposure to the anterolateral skull base through small craniectomies, avoiding excessive brain retraction injury and complications associated with long hospitalization [ 8 , 11 , 12 , 13 , 15 , 17 , 20 , 22 , 23 , 24 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since TOAs are minimally invasive approaches, in-depth anatomical knowledge is required to recognize the main landmarks despite the unusual surgical perspective, especially for young trainees. This corridor is indicated in the cases of proptosis and lesions located lateral to the CN II [ 8 , 13 , 17 , 19 , 20 , 23 , 24 , 31 , 39 , 53 , 54 , 57 ]. The TOAs offer a good exposure to the anterolateral skull base through small craniectomies, avoiding excessive brain retraction injury and complications associated with long hospitalization [ 8 , 11 , 12 , 13 , 15 , 17 , 20 , 22 , 23 , 24 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The endoscopic transorbital approach has now entered the skull base neurosurgeon's armamentarium for the management of selected skull base lesions (Somma et al, 2021 ; Yoo et al, 2021 ; Han et al, 2023 ). Starting from anatomic studies that demonstrated the feasibility of exploring via the transorbital route, the anterior (Di Somma et al, 2018 ; Nannavecchia et al, 2021 ; Lim et al, 2022 ), middle (Chibbaro et al, 2021 ; Guizzardi et al, 2022 ; Corvino et al, 2023 ), and posterior cranial fossae (De Rosa et al, 2022 ), many applications of this approach in the management of extradural lesions have been published (Dallan et al, 2018b ; Zoia et al, 2018 ; Park et al, 2020a ; Corvino et al, 2022 ; Lee et al, 2022 ; Lim et al, 2022 ; Noiphithak et al, 2022 ; Di Somma et al, 2023a ; Zoli et al, 2023 ), demonstrating the possibility of overcoming many concerns attributed to this approach in terms of poor maneuverability and intraoperative complications' management (Kim W. et al, 2021 ; Di Somma et al, 2023b ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also suggested the endoscopic transorbital approach (ETOA) to be considered for COLs. [20][21][22][23] In detail, the Joseph et al's study illustrated that ETOA could be used to remove selected spheno-orbital and medial sphenoid wing meningiomas. [23] Besides, Alberto et al [22] illustrated that the superior eyelid transorbital approach supraorbital approach can be used for spheno-orbital and intraconal meningiomas.…”
Section: Classi Cation and Surgical Approach Selectionmentioning
confidence: 99%
“…[20][21][22][23] In detail, the Joseph et al's study illustrated that ETOA could be used to remove selected spheno-orbital and medial sphenoid wing meningiomas. [23] Besides, Alberto et al [22] illustrated that the superior eyelid transorbital approach supraorbital approach can be used for spheno-orbital and intraconal meningiomas. Their studies thought ETOA should reduce the need for temporal lobe retraction and the extensive mobilization and reconstruction of the temporalis muscle.…”
Section: Classi Cation and Surgical Approach Selectionmentioning
confidence: 99%
See 1 more Smart Citation